2006
DOI: 10.3347/kjp.2006.44.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal protozoan infections and echinococcosis in the inhabitants of Dornod and Selenge, Mongolia (2003)

Abstract: The status of intestinal parasitic infections and seroprevalence of cystic echinococcosis in the inhabitants in Dornod and Selenge, Mongolia, was observed with stool and serum samples from 165 and 683 residents from August 9 to August 15, 2003. A total of 10 inhabitants (6.1%) were found to be infected with protozoan cysts or oocysts by stool examinations; 7, 1 and 2 cases with Entamoeba coli, Giardia lamblia and Cryptosporidium parvum, respectively. A total of 62 people (9.1%) revealed significantly high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…There were a few other community studies about CE prevalence in Mongolia [16,17]. The screening using ELISA method involved limited number of participants in some selected areas, such as Khovd and Bayan-Ulgii [18], Tuv near Ulaanbaatar [19], Dornod and Selenge [20]. The US screening survey wasn't available before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a few other community studies about CE prevalence in Mongolia [16,17]. The screening using ELISA method involved limited number of participants in some selected areas, such as Khovd and Bayan-Ulgii [18], Tuv near Ulaanbaatar [19], Dornod and Selenge [20]. The US screening survey wasn't available before.…”
Section: Discussionmentioning
confidence: 99%
“…The US screening survey wasn't available before. Prevalence rates given by those studies vary from lowest 2.1% in Dornod (4/187) to highest 11.7% (58/ 496) in Selenge province [20]. Previously, only Khovd and Bayan-Ulgii provinces were screened for echinococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…In [2] notified, that 21.9% of 6465 slaughetred sheep were infected by Echinococcus spp. A total of 62 people (9.1%) revealed significantly high levels of specific antibiodies against Echinococcus granulosus by enzyme-linked immunosorbent assays (ELISA) [25]. In the study of [10] they reported, that from total 1707 serum samples were 9.2% (31 out of 338) goat, 3.6% (21 out of 590) of sheep and 5.9% (46 out of 779) cattle shown aimag.…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…Both test showed high compliance-the ELISA detected 24% infectious rate, seems to be more specific than the LAT detected 16.5% infectious rate in ovine samples. Cryptosporidiosis is a primary cause by oocysts of genus Cryptosporidium and diarrhoeal clinical features in humans are known in all over the world [47; 48] Two children were infected with Cryptosporidium parvum in Selenge aimag in Mongolia [25]. Some species of Cryptosporidium use a zoonotic transmission for human and animals [27].…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…Байран маллагаатай аж ахуйн нялх тугалд үүрэн ПГУ-аар шинжлэхэд 50% халдварлалттай байв [11]. Сэлэнгэ аймагт явуулсан судалгаагаар 115 хүүхдийн баасны дээжид фермент холбоот эсрэгбиемийн урвал (ФХЭУ)-аар 1.7% (2/115) халдварлалтайг тус тус илрүүлжээ [12]. Мөн Бүгд Найрамдах Солонгос Улс (БНСУ)-ын Өвчний хяналт сэргийлэлтийн төв (ӨХСТ), Халдварт өвчин судлалын үндэсний төв (ХӨСҮТ)-ийн хамтарсан судалгаагаар цочмог суулгалт шинж тэмдэгтэй 138 хүний өтгөн(баас)ий дээж шинжлэхэд 7 (5.07%) криптоспоридийн халдвартай байв.…”
unclassified